DEVELOPMENT AND CURRENT STATUS OF THE INTERNAL SETTLEMENT AT RUP “BMZ” - A. E. Nikiforov; A. V. Volkov; V. E. Sidorchuk; A. V. Voitovich (Литьë и металлургия)
New main stages of development of the internal settlement system at RUP ''BMZ” are considered